The Effectiveness of Control Policy of Subsidized Fuel Consumption in Java-Bali - Djunedi, Praptono (Badan kebijakan Fiskal, 2014)
It has been more than three decades that the government provided subsidized fuel. The cheap fuel price leads to consumption of the fuel increase. Although the government has implemented some policies, subsidy on fuel remains hike in the budget. Therefore, by issuing MEMR Regulation on Control of Fuel Consumption, the government implement control policy of subsidized fuel consumption on official vehicles and others. The goals of the policy are to control of the subsidy through reducing the use of low-quality fuel (RON 88). Refer to the above illustration, this paper aims to describe the effectiveness of the policy and to propose policy recommendations to be effective. To measure effectiveness of the policy, this paper uses paired t test. The tool to know whether a significant difference on subsidized and non subsidized fuel sales between before and after the policy implemented. Based on the results, it can be concluded that the policy is not effective. To be effective, it is proposed as follows (1) there is adequate fuel cost allocation for each official vehicle, (2) optimization of the vehicle’s benefit, (3) the policy needs strong monitoring system, and (4) there is sanction for those who violate the policy.